2014
DOI: 10.1080/08856257.2014.906979
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers’ perceptions on physical activity engagement for children and young people with intellectual disabilities

Abstract: model was used to inform semi-structured focus groups to explore physical activity of CYP with ID.Participants were 23 (9 male) teachers and teaching assistants, from 3 special educational needs (SEN) schools (1 = Primary, 2 = Secondary) within North West England. Three focus groups were held with between 6 and 8 participants, audio and video recorded and data transcribed. Data were inductively and deductively analysed using Nvivo and represented through pen profiles. Results: Three pen profiles were developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…There were a few reasons for CYP engaging in unstructured physical activities during break periods. First, it was partly due to their own preferences, which is in keeping with research conducted by Downs et al () and Einarsson et al (); and second, it was also dependent on the staff supervising. Shaun (teacher) noted:
In lunch and break times it’s not so much structure, its more probably down to the staff that are on the yard at the time really.
…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…There were a few reasons for CYP engaging in unstructured physical activities during break periods. First, it was partly due to their own preferences, which is in keeping with research conducted by Downs et al () and Einarsson et al (); and second, it was also dependent on the staff supervising. Shaun (teacher) noted:
In lunch and break times it’s not so much structure, its more probably down to the staff that are on the yard at the time really.
…”
Section: Resultssupporting
confidence: 77%
“…In addition to structured PA periods such as PE lessons and extra‐curricular opportunities, break and lunch(recess) are ideal times to be physically active (Fairclough, Beighle, Erwin, & Ridgers, ). Research has suggested that CYP with intellectual disabilities are more reliant on the school environment for their PA as community programmes are often limited or unsuitable to their needs (Downs et al, ; Einarsson et al, ). Similarly, the school setting may provide solutions to some of the social barriers to PA, which include: a lack of parental time to assist with activities; a lack of friends to enjoy activities with; and negative attitudes from others (McGarty & Melville, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recess provides a daily opportunity for discretionary PA in a safe, supervised environment. This is perhaps even more important for this population, where many barriers are perceived to exist to PA engagement outside the school environment (Downs et al, 2013;Downs et al, 2014). Participants within this study engaged in small group activities at generally low PA intensities.…”
Section: Implications For School Psychologistsmentioning
confidence: 99%
“…Recent, formative, qualitative studies have suggested that opportunities for children and young people with ID are limited outside the school setting in the UK (Downs, Boddy, Knowles, Fairclough, & Stratton, 2013;Downs et al, 2014), and that schools represent the most accessible opportunity for children and young people with ID to be physically active.…”
Section: Intellectual Disabilities and Recessmentioning
confidence: 99%
“…Verbatim transcripts were read and re-read to allow familiarisation of the data and then imported into the QSR NVivo 10 software package. The authors then followed the pen profiling protocol which is detailed in previous studies (Mackintosh et al 2011, Boddy et al 2012, Ridgers et al 2012, Downs et al 2014. In summary, using the focus group questions as a guide, themes were created using deductive analysis.…”
Section: Discussionmentioning
confidence: 99%